Adopting an enterprise resource planning system in village government - Restu, Arnold; Gamayuni, Rindu Rika; Yuliansyah, Yuliansyah (Journal of Governance and Accountability Studies, 2024)
Purpose: The obligation of the Village Government to realize accountability and transparency of rural funds "forced" the village to use the ERP system. This study investigates the characteristics of technologies, individuals, and organizations that influence user decisions to adopt systems that will impact their performance. Research methodology: The technology acceptance model (TAM) was used to understand the factors that influence the adoption of the system and its impact on user performance. Data obtained from 72 users spread in Lampung Province. Results: The results showed that the compatibility of the system significantly influence the perceived usefulness. Facilitating conditions has a significant effect on perceived ease of use. Perceived usefulness and perceived ease of use has positive effect on symbolic adoption. Symbolic adoption significantly affects the user’s performance positively. Implementation: The implementation of this study involves a mixed-methods approach, including a survey and interviews with users and stakeholders, as well as a case study analysis of successful ERP implementations in village governments. Contribution: The contribution of this research is the identification of factors that contribute to successful ERP implementation in village governments, which can inform future adoption decisions and improve user performance.